178 - THE IMPORTANCE OF NURSING CARE IN WOUND HEALING: REVIEW OF LITERATURE (Fiep Bulletin - online, 2011)
Nursing care in wound healing, whether in primary, secondary or tertiary care services, must pay attention to the investigation of local, systemic and external factors contributing to the appearance and chronicity of the lesions, interfering with the healing process. The aim of this review is to characterize the scientific production published in the Virtual Health Library on nursing care in wound healing by author of the research, publication year, category of authors, study type approach, related subject, theme, the periodic in which the paper was published and site of search. The research is of an exploratory descriptive kind (review of literature) and quantitative approach, carried out in electronic databases available on the VHL (LILACS, MEDLINE, SCIELO e BDENF), the descriptors used for data collection were "nursing care" and "wound healing". During the collection, there were found a total of 7 articles distributed as follows: 4 on LILACS, 1 on MEDLINE and 2 on BDENF. The data collected were sketched on a table for better visualization and understanding. According to the survey, most studies were located in LILACS (57.1%), and were made in the years of 2002 (28.6%) and 2008 (28.6%), were produced by teachers (100.0%) and post-graduation students (57.1%), using the descriptive study (57.1%) and literature review (42.9%), with a qualitative approach (85.7%). The issue that predominated in most articles was the evaluation of the nurse in wound healing. In relation to the periodic to which they were linked, the Archive Ciência Saúde accounted for most of the articles. And the site that had published more was the state of São Paulo, through the cities of São José do Rio Preto and Ribeirao Preto. Nurses, as health professional and one of the responsibles for care with patients with wounds, have been searching for prevention strategies, evaluation and treatment for the control and approach of injuries, aiming to promote an environment that supports effective healing, without further complications or commitments.
Keywords: wound healing; nursing care; review